Multifactorial Modulation of Food-Induced Anaphylaxis - Benedé, Sara; Garrido-Arandia, María; Martín-Pedraza, Laura; Bueno, Cristina; Díaz-Perales, Araceli; Villalba, Mayte (Frontiers in Immunology, 2017)
Prevalence of food-induced anaphylaxis increase progressively and occurs in an unpredictable manner, seriously affecting the quality of life of patients. Intrinsic factors including age, physiological and genetic features of the patient as well as extrinsic factors such as the intake of drugs and exposure to environmental agents modulate this disorder. It has been proven that diseases such as mastocytosis, defects in HLA or filaggrin genes, increase the risk of severe allergic episodes. Certain allergen families such as storage proteins, lipid transfer proteins (LTPs), or parvalbumins have also been linked to anaphylaxis. Environmental factors such as inhaled allergens or sensitization through the skin can exacerbate or trigger acute anaphylaxis. Moreover, the effect of dietary habits such as the early introduction of certain foods in the diet, and the advantage of the breast-feeding remain as yet unresolved. Interaction of allergens with the intestinal cell barrier together with a set of effector cells represent the primary pathways of food-induced anaphylaxis. After an antigen cross-links the IgEs on the membrane of effector cells, a complex intracellular signalling cascade is initiated which leads cells to release pre-formed mediators stored in their granules that are responsible for the acute symptoms of anaphylaxis. Afterwards they can also rapidly synthesize lipid compounds such as prostaglandins or leukotrienes. Cytokines or chemokines are also released, leading to the recruitment and activation of immune cells in the inflammatory microenvironment. Multiple factors that affect food-induced anaphylaxis are discussed in this review, paying special attention to dietary habits and environmental and genetic conditions.